Hsa-miR-206b Involves in the Development of Papillary Thyroid Carcinoma via Targeting LMX1B. (15th March 2022) - Lu, Hongsheng; Zhu, Chumeng; Ruan, Yanyun; Fan, Lilong; Ruan, Zhengying; Chen, Qi; Yuan, Jiuyun; Xu, Yang; Wang, Hongwei; Wei, Qing
Abstract : Objectives . Papillary thyroid carcinoma (PTC) is the most common endocrine system malignant thyroid cancer, and patients with lymph node metastasis typically exhibit poor prognosis. MicroRNAs (miRNAs) can act as either oncogenes or tumor suppressors in PTC. This study was aimed at using PTC transcriptome data obtained from The Cancer Genome Atlas (TCGA) to identify differentially expressed, survival-related miRNAs and target genes. Methods . We analyzed the TCGA datasets to identify differentially expressed mRNAs/miRNAs in 493 PTC patients with stage I_II group (stages I and II) versus stage III_IV group (stages III and IV) according to TNM staging. The Kaplan-Meier survival analysis, the Cox regression analysis, and the log-rank test were performed to investigate survival-related miRNAs. Results . We identified 36 significantly differentially expressed miRNAs in the stage I_II group versus the stage III_IV group, in which 31 were upregulated and only 5 were downregulated (i.e., hsa-miR-891a-5p, hsa-miR-892a, hsa-miR-888-5p, hsa-miR-891b, and hsa-miR-892b). Additionally, five signature miRNAs (hsa-miR-206, hsa-miR-299-3p, hsa-miR-299-5p, hsa-miR-496, and hsa-miR-509-3-5p) were associated with the overall survival of PTC patients. We also found that LMX1B, whose expression was inversely correlated with hsa-miR-206 expression, was a putative target gene of hsa-miR-206 and LMX1B was likely to serve as a tumor suppressor in PTC. Conclusion . hsa-miR-206b might be involved in promoting TNM staging in PTC via targeting of LMX1B .